Moderate Fever Cycles as a Potential Mechanism to Protect the Respiratory System in COVID-19 Patients - Guihur, Anthony; Rebeaud, Mathieu E.; Fauvet, Bruno; Tiwari, Satyam; Weiss, Yoram G.; Goloubinoff, Pierre (Frontiers in Medicine, 2020)
Mortality in COVID-19 patients predominantly results from an acute respiratory distress syndrome (ARDS), in which lungs alveolar cells undergo programmed cell death. Mortality in a sepsis-induced ARDS rat model is reduced by adenovirus over-expression of the HSP70 chaperone. A natural rise of body temperature during mild fever can naturally accumulate high cellular levels of HSP70 that can arrest apoptosis and protect alveolar lung cells from inflammatory damages. However, beyond 1–2 h of fever, no HSP70 is being further produced and a decreased in body temperature required to the restore cell's ability to produce more HSP70 in a subsequent fever cycle. We suggest that antipyretics may be beneficial in COVID-19 patients subsequent to several hours of mild (<38.8°C) advantageous fever, allowing lung cells to accumulate protective HSP70 against damages from the inflammatory response to the virus SARS-CoV-2. With age, the ability to develop fever and accumulate HSP70 decreases. This could be ameliorated, when advisable to do so, by thermotherapies and/or physical training.